STRATEGI GURU DALAM PROSES PENANAMAN NILAI SOSIAL TERHADAP BAHAYA PERGAULAN BEBAS DI SMAN 4 SOPPENG - Rifdan; Bakhtiar; Zikrina Nur Insyani Masri (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2024)
This research aims to determine (1) Teacher strategies in the process of instilling social values against the dangers of promiscuity at SMAN 4 Soppeng, (2) Teacher actions towards students who have fallen into promiscuity at SMAN 4 Soppeng. In order to achieve this goal, the researcher used this type of research, which is qualitative research using a descriptive approach, therefore, in order to achieve a research goal, data collection techniques were used, namely observation, interviews, documentation. The informants for this research were 3 teachers consisting of a Guidance Counseling teacher, a Social Studies teacher who was also the homeroom teacher and a Civics Teacher and 3 students. The research results show that: (1) The teacher's strategy for instilling social values is to form discipline towards students, communicate well, teach the importance of mutual respect, and provide an understanding of religion. (2) The actions given by the teacher are able to create awareness for students even though these actions are not as expected. Actions taken by teachers include taking approaches to provide warnings or advice that can create awareness for students. Therefore, the role of a teacher in instilling social values at school has been applied to students. Keywords: Strategy, Action, Awareness